Números primos e criptografia: do conceito ao sistema RSA - Silva, Valéria Batista da (Universidade Federal do Tocantins, 2020)
This dissertation aims to present prime numbers and cryptography for Basic Education through teaching activities. Thus, an experience lived in the Graduate Program tutoring class and proposals for activities to teachers are displayed. In the educational field, the work aims to encourage teachers to reflect on how to teach prime numbers combined with cryptography, emphasizing that these are essential for the creation of public keys in the RSA cryptographic system. For the development of the research it was necessary to perform a bibliographic search to allow an exploration of the concept of numbers and cryptography; We also develop teaching activities as a teaching experience and propose